Proteolytic degradation of seed proteins of vetch species (Vicia L. subgenus Vicia) of section Peregrinae Kupicha during SDS-electrophoresis and its prevention - A. V. Konarev; E. E. Eggi; T. G. Aleksandrova (Биотехнология и селекция растений, 2024)
Background. Due to its simplicity and good reproducibility, SDS-electrophoresis of seed proteins is widely used for investigating the gene pool of legumes and other plants, for species and varietal identification, analyzing the intraspecific variability, and registering collection material. The data obtained by this method agree well with the DNA analysis results complement them. Typically, legume seed proteins, including representatives of the genus Vicia L., show clear informative SDS electrophoretic profiles. When analyzing seed accessions of vetch species of the section Peregrinae Kupicha using standard approaches previously developed at VIR and approved by ISTA (the International Seed Testing Association), clear electrophoretic protein profiles could not be obtained for many accessions. This called into question the applicability of standard approaches to identifying vetch species in the section Peregrinae. The objective of the work was to clarify the nature of seed proteins degradation in representatives of the Peregrinae section and to find ways to prevent it to ensure the possibility of carrying out species identification and registration of all accessions in the vetch collection using a unified approach. Material and methods. Seed proteins of a number of vetch species Vicia L. from sections Bithynicae (B. Fedtsch.) Maxted, Hypechusa (Alef.) Aschers. et Graebner, Microcarinae Maxted and Peregrinae, members of the subgenus Vicia, were analyzed by SDS-electrophoresis using the standard method of protein extraction from flour with 0.025 M Tris-glycine buffer pH 8.3 at room temperature and its modifications, including heating the extract at 80°C or 100°C with or without the addition of 2-mercaptoethanol, as well as the addition of cysteine and serine protease inhibitors. Results and discussion. An analysis of seed proteins of representatives of most sections of the subgenus Vicia yielded informative species-specific protein profiles, whereas species of the section Peregrinae were characterized by the protein profiles, which indicated protein degradation, and species of this section differed in the frequency of such profile occurrence. While such profiles were obtained for all seeds of seven accessions of V. aintabensis Boiss & Hausskn. ex Boiss differing in geographical origin, year and place of regeneration, and 12 out of 13 of V. peregrina  L. accessions demonstrated profiles of partially or completely degraded proteins, complete seed protein profiles were obtained for six out of nine V. michauxii Sprengel accessions. A change in conditions for protein isolation, namely replacement of their extraction from flour with Tris-glycine buffer pH 8.3 at room temperature with extraction in the same buffer by a short-term heating at 100°C in the presence of 2-mercaptoethanol, made it possible to obtain complete protein profiles for all accessions representing the section Peregrinae. The protein profiles of representatives of other vetch sections, as well as the profile of soybean proteins used as a standard for legume species identification, did not differ from the original ones under the modified conditions. Conclusions. The obtained results suggest that protein degradation in species of the Peregrinae section is associated with the abnormal activity of endogenous seed proteases under standard protein extraction conditions, and this trait is determined genotypically. A new modification of the method for isolating proteins from seeds makes it possible to apply the generally accepted approaches based on SDS-electrophoresis in the analysis of the gene pool of the Peregrinae section of the subgenus Vicia, as well as other vetch species.